Kewarisan Anak di Luar Perkawinan di Tengah Isu Gender - Wahidah, Wahidah (Jurnal Muadalah, 2013)
Child outside of marriage is essentially a term that sense rather difficult to be correlated with the term natural child ( ibn al mulaanah ) as fikih.This dificulty provision was triggered by the